The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s40560-016-0134-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of a modified early warning score system to reduce the rate of in-hospital cardiac arrest

Abstract: BackgroundPhysiological abnormalities are often observed in patients prior to cardiac arrest. A modified early warning score (MEWS) system was introduced, which aims to detect early abnormalities by grading vital signs, and the present study investigated its usefulness.MethodsBased on previous reports, the Chubu Tokushukai Hospital-customized MEWS was developed in Okinawa, Japan. The MEWS was calculated among all inpatients, and the rates of in-hospital cardiac arrests (IHCAs) were compared according to the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 17 publications
0
33
0
4
Order By: Relevance
“…When the total score reached 7, nurses and doctors conducted relevant treatment. The results confirmed that MEWS can effectively reduce the rate of cardiac arrest in inpatients [17]. There are few general departments applying MEWS in China, and most of them focus on the studies of single department [18] [19] or single disease [20] [21], such as the use of MEWS in cardiology, and the application value of MEWS in cardiac arrest patients, etc.…”
Section: Specific Departments Applicable To Mewsmentioning
confidence: 58%
See 1 more Smart Citation
“…When the total score reached 7, nurses and doctors conducted relevant treatment. The results confirmed that MEWS can effectively reduce the rate of cardiac arrest in inpatients [17]. There are few general departments applying MEWS in China, and most of them focus on the studies of single department [18] [19] or single disease [20] [21], such as the use of MEWS in cardiology, and the application value of MEWS in cardiac arrest patients, etc.…”
Section: Specific Departments Applicable To Mewsmentioning
confidence: 58%
“…Dynamic MEWS score can better reflect patients' conditions in real time [8]. Nishjima once evaluated the MEWS once a day for all patients in the general department, the corresponding physiological indicators recorded into the nursing system, by the system automatically calculate the MEWS score, when reached 7 points, the system automatically alarm, ward nurses need to report the attending doctor, for the treatment of patients, during which continue to evaluate three times a day, if discover the patients need a higher level of medical care facilities, are immediately turned to ICU, unless the patient give up treatment agreement (Do Not Resuscitate, DNR) [17]. Most domestic studies have studied the degree of prediction of disease changes in patients with a certain static MEWS score, with the most related studies on single score at admission [22].…”
Section: Dynamic Mews Can Better Reflect Patients' Conditionsmentioning
confidence: 99%
“…Intervensi yang baik pada pasien yang mengalami emergensi medik di ruangan dan monitoring ketat pada pasien yang menunjukkan gejala emergensi medik secara dini akan menurunkan skor rerata APACHE II pada pasien ICU dengan asal admisi ruangan. 9 Rerata lama perawatan di ICU RSUP Dr. Hasan Sadikin Bandung adalah 9,89 hari. Faktor yang memengaruhi lama perawatan adalah faktor institusi, faktor medis, faktor sosial, dan faktor psikologis.…”
Section: Pendahuluanunclassified
“…However, it was reported that in 358 American hospitals, the total number of in-hospital cardiac arrests (IHCA) was 102,153, and the number of IHCA cases per 1000 admissions was 4.02 (IQR 2.95-5.65), and the most important factor to improve case-survival rate was a hospital's nurse-to-bed ratio [14]. Furthermore, in Japan, Nishijima reported the incidence of IHCA before and after introduction of the modified early warning score (MEWS) [15]. Although the incidence of IHCA was significantly decreased after introduction of the MEWS system (before the introduction of the MEWS system, 5.21%/15months versus after introduction, 2.39%/15 months; p < 0.01), the risk of IHCA remained.…”
Section: Study Limitationsmentioning
confidence: 99%